Sediment Features and Human Activities Structure the Surface Microbial Communities of the Venice Lagoon - Banchi, Elisa; Del Negro, Paola; Celussi, Mauro; Malfatti, Francesca (Frontiers in Marine Science, 2021)
The microorganisms that live in the top sediment layer play essential roles in marine ecosystems, influencing different dynamics such as the deposition and processing of organic matter, biotic activities, and nutrient cycling. Analyzing these benthic microbial communities is crucial to evaluate and predict how environmental conditions and climate changes will affect marine biodiversity and biogeochemistry. The Venice Lagoon is one of the largest and important Adriatic transitional systems and it is subjected to different and extensive natural and anthropogenic stressors. In this study, the microbial communities living in the top centimeter of Lagoon sediments were finely characterized using 16S rRNA gene amplicon sequencing and metagenomics. Samples were collected seasonally in 2019 and 2020 at five sites covering the different sub-basins of the Lagoon. The data provided new insights into the microbial spatial and temporal dynamics in terms of biodiversity, functions, and metabolisms. We also focused on the biogeochemical cycles of carbon, nutrients, metals, antibiotics, and xenobiotics from the macro- to the micro-scale. Our results indicated a clear and stable spatial distribution of sediment communities at the different sites. Salinity, grain size, and total organic carbon were found to be important drivers in the composition and structure of the communities. We detected high diversity and differences at the ecosystem level in carbon fixation and carbon flow strategies, as well at the microscale level concerning mobilome and cell signaling. We showed that anthropogenic-related pressure influence both taxonomy and potential functions of the microbial communities, with persistently polluted areas representing hotspots of resistance genes toward toxic compound and antibiotics. Our findings highlighted that sediment features and human-related activities have profound and long-term impacts on the benthic microbial communities of the Venice Lagoon, with potential implications in sediment management strategy.